The Influence of Financial Literacy and Non-Cash Payments on the Consumptive Behavior of Students in Jabodetabek - Efriyanto Efriyanto; Rodiana Rodiana; Lufita Anggun; Erwin Permana; Harnovinsah Harnovinsah; Rofiq Idris (Dinasti Publisher, 2026)
This study aims to analyze the influence of financial literacy and the use of cashless payment systems on the consumer behavior of students in the Jabodetabek area. With the development of financial technology, students' understanding of financial literacy is becoming increasingly important in managing their personal finances. Furthermore, the widespread use of cashless payment methods can influence spending patterns and consumption habits. Currently, students have been swept up in the digital transformation, especially in financial transactions, with many transactions conducted using cashless platforms such as GoPay, Shopee Pay, and others. The method used was a quantitative survey approach with 100 students in Jabodetabek. The research instrument was a questionnaire to measure financial literacy, cashless usage, and consumptive behavior.